Is pre‐operative imaging of external angular dermoid cysts in children necessary?. (4th May 2022) - Mead, Jessica; Kirkpatrick, Joshua; Murdoch, Jean; Stringer, Mark D
Abstract : Aim: To investigate the frequency and modality of pre‐operative imaging in children with an external angular dermoid cyst and whether this influenced subsequent management. Methods: A retrospective study was undertaken to assess the presentation, investigation, treatment and outcomes in children aged less than 16 years with an external angular dermoid cyst. All children who underwent external angular dermoid cyst excision between January 2008 and April 2021 at a regional children's hospital were analysed. Results: Sixty‐one patients (32 boys) were identified. Fifty‐four were managed by paediatric surgeons and seven by ophthalmic surgeons. Pre‐operative imaging was performed in 19 (31%) patients, including plain radiographs (3), ultrasound scan (14), computerised tomography scan (1), and magnetic resonance imaging scan (2). None of these investigations showed evidence of an intracranial or orbital extension of the cyst or changed management. All cysts were excised under day‐case general anaesthesia. There was one minor postoperative complication and two recurrences. Conclusions: External angular dermoid cysts rarely communicate through the bone with the orbit or anterior cranial fossa. Routine pre‐operative imaging is unnecessary unless there are clinical features such as an atypical location (e.g. temporal), eye signs (e.g. strabismus, proptosis and globe displacement) or a draining sinus.